The Institutional Role of Slum Management in Denpasar City Area - Wijaya Putra, Anak Agung Gde Sutrisna; Paturusi, Syamsul Alam; Putra, I Nyoman Darma; Kumbara, Ngr. Anom (Ridwan Institute, 2024)
The limited availability of land in major cities like DKI Jakarta, Surabaya, and Denpasar City has forced residents to compromise on ideal settlement locations, leading to a switch in land use patterns. Failure to secure ideal locations exacerbates settlement issues, ultimately contributing to the proliferation of urban slums. Denpasar City, in particular, grapples with various problems stemming from slum growth. As part of its responsibilities in urban development, the government is tasked with providing public services, safeguarding low-income communities, promoting regional growth, ensuring environmental sustainability, and upholding national integrity. However, the phenomenon of migrant influx in Denpasar City presents an additional challenge for governance. Traditional villages play a pivotal role in managing migrant populations by leveraging pecalang (traditional Balinese security forces) and customary rules to maintain community cohesion. To effectively address slum proliferation, customary villages must align their development goals and strategies. This qualitative research utilizes primary and secondary data to explore the role of institutions in slum management. Despite various programs aimed at mitigating urban challenges, the effectiveness of institutions like the PKP Working Group and DLHK remains suboptimal. Therefore, there is a pressing need for customary villages to play a more active role in tackling slum issues within their jurisdictions.